Ethnomathematics: An approach to teacher perception in aboriginal communities in Peru (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Ethnomathematics is the new approach that has mathematical education to favor learning in students of differenteducational levels. It is understood epistemologically as a teaching method that seeks to understand the different ways ofknowing different minority cultures during a globalized society. For this reason, the objective was to interpret the experiencesof the mathematics teachers of the Santa Clara of Uchunya community of Peru concerning ethnomathematics work.Methodologically, the research was approached from a qualitative perspective, making use of the interpretative paradigmthrough the ethnomethodological method. This research allowed the recognition of four units of analysis for the presentation ofthe results: a) Traditional mathematics and ethnomathematics, irreconcilable?; b) Ethnomathematics and knowledgemanagement, fundamental pillars for the rescue of ancestral culture; c) Importance of ethnomathematics in the training processof Aboriginal students; d) Future challenges of ethnomathematics for the achievement of quality and inclusive education inPeru. The interpretation of the findings raises new questions: How can universities manage ethnomathematics trainingprograms to achieve social gaps? Are Peruvian universities ready to transform their curricula and include training inethnomathematics? What will be the policies of the Peruvian State to reduce social gaps through the implementation ofethnomathematics programs? What will be the educational reality in other Aboriginal populations regarding the perception ofethnomathematics?.